Assess the Attitude of Adult towards Mentally Ill - Thomas, Shiji; Vijyan, Archana; Thomas, Elizabeth; Tomy, Jeena; Joy, C. J. Neethu; Joseph, Nimmy; Sunny, Sandra (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Mental health is an integral and essential component of health. Mental illness is a state of imbalance between the individual and the surrounding world, a state of disharmony between oneself and others, a co-existence between the realities of the self. Mental illnesses are some least understood condition in society. Mental illness have been largely ignored or neglected because of the communities perception and the attached social stigma existing in the society. Mental illness is an adjustment in living others attitude strongly influence the mentally ill person. So a positive attitude provides a support to them. Objectives: To assess the attitude of the adult towards mentally ill, to determine the association of attitude with socio-demographic characteristics of adults. Method: A descriptive research design was used for the present study. The sample consists of of100 adults. The attitude scale is used to assess the attitude of adults towards mentally ill. Data were analysed by using descriptive statics, inferential statistics. Results: The findings of the study showed that out of 100 adults. 68% of the subject had favourable attitude, 31% had moderate attitude and 1% had unfavourable attitude. There is a significant association of attitude with education and occupation.